Księgarnie, ich asortyment i usługi w cyfrowym środowisku sieciowym = Bookstores, their product range, and services in the digital network environment - Góralska, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article discusses the phenomenon of the online book trade. It attempts to categorize bookstores and to determine the basic directions of their development. It discusses the specifics of the product range offered by e-bookstores, as well as the tools for helping customers reach specific products. In terms of services, the emergence of new areas of activity for bookstores is emphasized.
Keywords: handel internetowy; księgarnie; księgarnie internetowe; księgarstwo; usługi; usługi cyfrowe